Теоретично-методичні підходи до оцінки інвестиційної привабливості регіонів України - Соколова, Л. В.; Литвинова, А. В. (2021)
Currently, when the Ukrainian economy is developing in an unstable, uncertain, aggressive, dynamic external environment, there is an urgent need to increase the level of investment attractiveness of each region of the country and, as a consequence, the need to increase attention to scientific and methodological support for assessing the integral indicator of investment attractiveness region.
Theoretical and methodological approaches to evaluation of investment attractiveness of regions of Ukraine
DOI: https://doi.org/10.32843/infrastruct54-28
Keywords: investments; nvestment attractiveness of the region; assessment indicator; statistical indicator; integral assessment; інвестиції; інвестиційна привабливість регіону; індикатор оцінки; статистичний показник; інтегральна оцінка